Synthesis, Spectral and Thermal Properties of Hydrazinium, Aminoguanidinium and Pyridinium Uranyl Pyridine-2,6-Dicarboxylates - Hussain, T.M. Ahamed; Sivasankar, B.N. (Asian Journal of Chemistry, 2020)
Anionic complexes, pyridine-2,6-dicarboxylato uranylate containing protonated weak bases such as hydrazine, guanyl hydrazine and pyridine as charge neutralizing entities have been isolated from aqueous solution containing respective bases, dipicolinic acid and uranyl nitrate hexahydrate. The molecular compositions and structural geometries have been assigned by analyzing their elemental analyses, spectral data and thermal patterns and the molecular formulae, A2[UO2(PDC)2] where A= N2H5 +/ AGH+ (aminoguanidinium) or PYH+ (pyridinium) cation and PDC = pyridine-2,6-dicarboxylate dianion has been proposed for the newly synthesized coordination compounds. Oxidative degradation in air yielded U3O8 as the residue, which has been proposed on the basis of thermogravimetric weight loss and powder XRD pattern. Based on the spectral results and careful analyses, a hexagonal bipyramidal geometry has been assigned for all the three uranyl(II) complexes.